2020
DOI: 10.1038/s41467-020-16284-8
|View full text |Cite
|
Sign up to set email alerts
|

Genomic adaptations to aquatic and aerial life in mayflies and the origin of insect wings

Abstract: The evolution of winged insects revolutionized terrestrial ecosystems and led to the largest animal radiation on Earth. However, we still have an incomplete picture of the genomic changes that underlay this diversification. Mayflies, as one of the sister groups of all other winged insects, are key to understanding this radiation. Here, we describe the genome of the mayfly Cloeon dipterum and its gene expression throughout its aquatic and aerial life cycle and specific organs. We discover an expansion of odoran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 78 publications
1
61
0
Order By: Relevance
“…Niwa et al (2010) found that some wing genes are indeed expressed in these tissues. More recently, Almudi et al (2020) demonstrated a large overlap in the transcriptome of wings and abdominal gills in the mayfly Cloeon dipterum . The developmental origin of these abdominal tissues (specifically whether they are of tergal or pleural origin) and their Hox regulation have yet to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Niwa et al (2010) found that some wing genes are indeed expressed in these tissues. More recently, Almudi et al (2020) demonstrated a large overlap in the transcriptome of wings and abdominal gills in the mayfly Cloeon dipterum . The developmental origin of these abdominal tissues (specifically whether they are of tergal or pleural origin) and their Hox regulation have yet to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…For all insects (including mosquitoes), the mean genome size in the Animal Genome Size Database is 1077 Mbp ( n = 1345; accessed 13 July 2020) [ 26 ]. While aquatic insects are poorly represented in the Animal Genome Size Database, sequencing-based reports of their genome sizes include five taxonomic orders with a mean size of 600 Mbp ( n = 20) [ 27 , 28 , 29 , 30 , 31 ]. Thus, there is no evidence that aquatic insect genomes are particularly large and unwieldy when compared to their terrestrial counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…For all insects (including mosquitoes), the mean genome size in the Animal Genome Size Database is 1077 Mbp (n = 1,345; accessed 13 July 2020) [22]. While aquatic insects are poorly represented in the Animal Genome Size Database, sequencing-based reports of their genome sizes include five taxonomic orders with a mean size of 600 Mbp (n = 20) [23][24][25][26][27]. Thus, there is no evidence that aquatic insect genomes are particularly large and unwieldy when compared to their terrestrial counterparts.…”
Section: Resultsmentioning
confidence: 99%